Comprehensive review of Sumbulut Teeb (Nardostachys jatamansi DC.) and its organoleptic evaluation of three samples available in the market: Shifka W.*, Fahamiya N., Shiffa M. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Sumbulut Teeb (Nardostachys jatamansi DC) belonging to the family Valerianaceae is commonly known as Balchar, Iatamashi or Indian spikenard, is an erect perennial herb. The main parts used are rhizome and rhizome oil. Because of high commerce, the rhizome of Nardostachys jatamansi is often subjected to adulteration with other drugs but it is essential to use genuine drugs for better therapeutic effects. Therefore, the present study is proposed to verify the Sumbulut Teeb available in the market to detect adulteration and to get the genuine drug. A systematic literature review has been carried out to gather authentic information on Sumbulut Teeb from Unani and Ayurveda classical text, Unani and Ayurveda Pharmacopeias, ethno-botanical literature, scientific journals and from the web through the macroscopic description. The rhizome samples available in the name of Jatamansi were collected from the market. The samples were subjected to organoleptic evaluation. The obtained results were verified by comparing the data available in the Unani Pharmacopoeia of India. The study revealed that Sumbulut Teeb possesses Antispasmodic, Diuretic, Carminative, Stomachic, Sedative, Antihistaminic, Anti-arthritic, Analgesic Anti-fungal and Anti-bacterial pharmacological activities. Further, it is a mouth freshener, tonic and stimulant. The organoleptic evaluation revealed that the market samples available under the name of Jatamansi is not actual Sumbulut Teeb. The sample available as Jata makutu is the genuine Sumbulut Teeb. However, further physiochemical, phytochemical and chromatographic investigations are needed to authenticate the genuine Sumbulut Teeb to prevent adulteration and to obtain and maintain the high quality of this plant products.